KARAKTERISTIK DAN POLA PERSEBARAN DOLINA DI KECAMATAN PONJONG DAN SEMANU, KABUPATEN GUNUNGKIDUL - Damayanti, Astrid; Sari, Diah Fitri Novita (UI Scholars Hub, 2018)
Ponjong and Semanu Districts, Gunungkidul Regency are included in Gunung Sewu Karst mega system which has the variety of morphologies. Karst morphologies were formed as the result of karstification that could have negative impacts, such as doline’s modification impacts land subsidence occurrence. Therefore, the aim of this research is to know the potential of land subsidence by determining characteristics and distribution pattern of doline. Those characteristics of doline are karst terrain, vegetation density, and surface temperature. This research used SRTM data and Landsat 8 to identify those characteristics of doline. Furthermore, using analysis doline’s morphometric and Nearest Neighbour Analysis (NNA) method used to find the distribution pattern of doline. Based on its characteristics, doline is divided into wet and dry. Doline has three different shapes, which are oval, round, and irregular. Those dolines have the group distribution pattern (NNA index 0,843). In Semanu District formed a clustering pattern, indicating further development of karstification of doline when compared with in Ponjong District which still tend to be random. Characteristics of clumped doline are found in lowland terrain forms with medium vegetation densities and high surface temperatures, while random ones have a bumpy terrain field shape with dense vegetation densities and low surface temperatures.